Blood Transfusion is an Independent Risk Factor for Postoperative Serious Infectious Complications After Pancreaticoduodenectomy - Zhang, Liyang (World J Surg, 2016)
BACKGROUND/PURPOSE: Blood transfusionhas been considered as a risk factor for postoperative infection after major surgery. However, the relationship between perioperative blood transfusion and the development of serious infections after pancreaticoduodenectomy remains controversial. The purpose of this study was to analyze risk factors associated with postoperative serious infections following pancreaticoduodenectomy. METHODS: We conducted a retrospective study of 212 patients who underwent pancreaticoduodenectomy during past 2 years and assessed the risk factors for serious infectious complications. RESULTS: Serious infections developed in 61 patients (29 %) including 47 cases of surgical site infection (SSI), 19 cases of bacteremia, and 13 cases of pneumonia. One patient died of severe septic shock. A multivariate logistic regression analysis of perioperative factors identified that pancreatic fistula (P < 0.01, OR = 9.763) and blood transfusion (P < 0.01, OR = 3.216) were significant risk factors for serious infections. After excluding 46 patients with pancreatic fistula, blood transfusion continued to be an independent risk factor for serious infections (P < 0.01, OR = 5.831). CONCLUSION: Blood transfusion was the strongest independent factor for serious infections after pancreaticoduodenectomy, which should be considered a quality indicator for the performance of pancreaticoduodenectomy.